Evidences and Aspects of Forest Transition in India - Singh, M. P.; Bhojvaid, P. P.; Reddy, S. R.; Ashraf, Jawaid (Indian Forester, 2014)
The shift from decrease to a trend of increasing forest cover associated with economic development of a nation or to a geographical region is referred to as forest transition. Studies indicate that earlier stage of human development is marked by high forest cover and low deforestation but increase in incomes accelerate the rate of deforestation leading to loss of forest cover; but at incomes beyond a certain level, the rate of deforestation reduces; then the trend reverses and a slow increase in forest cover is seen. Evidences of Indian forest transition were tried to be traced from the Land Use and Land Cover Change for the period 1880-1980. Supplementing this data with the recent forest cover data of FSI from 1990 onwards, an attempt has been made to characterize forest transition in India. Deforestation was the dominating aspect in the initial temporal phase (till 1980), large scale afforestation/rehabilitation, social forestry and agro-forestry programmes of the state and central governments dominated the temporal phase of forest transition in India during the period of 1980-2000. Conservation and sustainable management of forests dominated the later phase 3 (Beyond 2000). Timber production from government forests gradually declined about 2 million m from the forests (excluding trees outside forests) in 2010 while most of the wood produced in the country come from trees outside forests (TOF) grown in private lands under agro-forestry, along the roads, canal, homesteads, etc. It's predicted that in a business as usual scenario, the forest transition in India will follow the trend as established in the last three decades and it is projected that the forest cover will increase to 71.34 million hectare in 2020. Forest transition trajectory in the forest transition curve indeed serves an easy instrument for testing the effectiveness of government interventions and policy implications.